Experiences on organisation of fruit and vegetable sector in Hungary - Felföldi, János (Applied Studies in Agribusiness and Commerce, 2009)
The objectives are (1) to reveal some current issues on organisations founded by fruit and vegetable producers and (2) to stress upon those factors that should be highlighted in the very next future. In Hungary, POs have been accounting for bigger share of fruit and vegetable trading in Hungary, which refers to a better organisation in the sector. Bargaining force and level of experience on running such businesses, although, are still much behind the level expected. Flexibility and speed of a running business are highly determined by the legal form of Pos. The most favourite form is cooperative that is not flexible enough as a business form, especially for starting businesses. Low yearly turnover and weak market power feature the POs, preferring short time solutions to strategic thinking. It is macro environmental factors that generate short term thinking, but coupled with mismanagement on different levels of corporate management.